EGFR p.V774M/p.L833V compound mutations in lung adenocarcinoma responded well to almonertinib: a case report - Pan, Hai; Zhang, Linlin; Meng, Fanlu; Guan, Shasha; Zhong, Diansheng (Frontiers in Oncology, 2023)
There are about 10-15% of uncommon EGFR mutations found in NSCLC patients, and their sensitivity to EGFR TKIs still lacks sufficient clinical evidence, especially for rare compound mutations. Almonertinib is the third generation of EGFR-TKIs that has demonstrated excellent efficacy in classical mutations, however, effects in rare mutations have also been rarely reported.Here, we report a patient with advanced lung adenocarcinoma with a rare EGFR V774M/L833V compound mutation, who achieved long-lasting and stable disease control after first-line Almonertinib targeted therapy. This case report could provide more information for therapeutic strategy selecting of NSCLC patients harboring rare EGFR mutations.